Maani Letters and Their Influence in Facilitating Islamic Jurisprudence Analytical Study of Waw Athaf Letters in Ahkam Verses/ حروف المعاني وأثرها في تيسير الحكم الفقهي واو العطف نموذجا، دراسة تحليلية في بعض آيات الأحكام - Abuzaid Mail, Wasfy Ashour; Baddiny, Ramdan Fawzy (Ijaz Arabi Journal of Arabic Learning, 2024)
The letters of meanings are a linguistic topic that the fundamentalists borrowed in the field of fundamentals, and they may have added appreciable additions to it to achieve the goal of lending it to science. This is because of its importance in deducing legal rulings. This appears in the way fundamentalists deal with it in their books, ancient and modern. But there is another essential feature, which is that the conjunctions, or the letters of meanings, by contemplating the places they appear in the verses of rulings - and the hadiths of rulings by extension - we found that they have an essential effect in deducing rulings on the one hand, and in facilitating jurisprudential rulings on the other hand. The fundamentalists have worked hard to explain the meanings of the letters of meaning, including the conjunctions, and to explain the impact of this on deducing legal rulings. They have made great efforts in doing so. They based many of the deduction rules on rules in the Arabic language. This research focuses on the letter waw, as it is one of the conjunctions of the meaning letters, and shows its effect in deriving legal rulings while presenting its role in facilitating jurisprudential rulings, which is consistent with the intention of the law and its will in basing rulings on facilitation.